Pengaruh pijat bayi terhadap peningkatan kualitas tidur bayi usia 3-10 bulan di Desa Tamanan wilayah kerja Puskesmas Banguntapan II - Suryati Suryati; Naelatur Rizqiyah; Eka Oktavianto (Riset Informasi Kesehatan, 2019)
Background: every parent wants a child who can grow and develop optimally according to its age category. One of the factors that can influence growth and development is the quality of sleep, due to 75% growth hormone produced when the baby sleeps. Sleep quality of babies can be stimulated through the act of giving massage baby. Objective: this study aims to determine the effect of infant massage on improvement the quality of sleep for infants aged 3-10 months in a village of Banguntapan Public Health Center II. Research method: this research is a pre-experiment research with an approach in one group (one-group pre-post test design without control). Data analysis used is the Wilcoxon test. This research was carried out in the Working Area Village Banguntapan II Health Center, with a population of 64 infants aged 3-10 months. Technique sampling using purposive sampling, which is the number of 15 babies aged 3-10 month. Providing education and demonstration of baby massage is done once, then massage done by parents of babies every day within 3 weeks, and observed by researchers every 2 days. Sleep quality was measured using the A Brief Screening Questionnaire For Infant Sleep Problems (BISQ). Results: Before being given massage the majority of the quality of bad baby sleep was 14 respondents (93.3%), then after being given massage for 3 weeks there was an increase in quality sleep where all babies have good sleep quality of 15 respondents (100%). Comparative test results infant massage between before and after massage is p value 0.000 (p value <0.005). Conclusion: there is the effect of infant massage on improving the quality of sleep for infants aged 3-10 months at Village of Bangutapan II Health Center.